Design and structural optimization of T-resonators for highly sensitive photoacoustic trace gas detection. (April 2022) - Liu, Lixian; Huan, Huiting; Mandelis, Andreas; Zhang, Le; Guo, Chengfei; Li, Wei; Zhang, Xueshi; Yin, Xukun; Shao, Xiaopeng; Wang, Duantian
Highlights: Multiple-gas tests by 30 mW broadband source at extraordinary 4.1 × 10 −10 NNEA value. Simultaneous gas fingerprinting and detecting with double optical-path enhancement. Quantitative external noise and Q-factor model ensures the optimized PA cell design. Digital denoising algorithms further suppresses noise and augments spectral quality. Abstract: Thanks to the available ultra-wide wavelength range compared with broadband laser sources, the use of blackbody radiators in photoacoustic spectroscopy features the simultaneous detection of multiple gas species in the presence of cross-interfering absorption lines. The major problem associated with broadband incoherent sources is less power and less stable intensity per wavenumber than lasers and leads to limited gas detection sensitivity. In this paper, the detectivity of a broadband double optical path differential photoacoustic system was enhanced with the development of dimension-optimized high-responsivity T-resonators for simultaneous multiple trace gas detection. Enhanced Q-factor and external noise suppression level constitute dual criteria for the optimization of T-resonators. Three digital signal processing algorithms were separately investigated which further improved gas dectectability. The capability of the multiple–trace-gas detection framework was verified by measuring CO2, C2 H2 and H2 O simultaneously. The spectral results processed by a wavelet denoising algorithm present the best performance in terms of background noise suppression and spectral feature fidelity. [ Q2.2 ] With the absorption enhancement of the optimized T-cells and background suppression of the wavelet denoising algorithm, a broadband differential photoacoustic system was achieved with only a 30 mW globar source and normalized noise equivalent absorption coefficient value of 4.1 × 10 −10 W·cm −1 ·Hz −1/2 which is two orders of magnitude improvement over the original T-cell-based photoacoustic configuration. The noise equivalent detection limits were found to be 223 ppbv for CO2, 625 ppbv for C2 H2 and 865 ppbv for H2 O, respectively.